Biodegradable chitosan scaffolds fabricated with protein-loaded microspheres for tissue engineering. - Lau, Ting Ting. (2009)
Current scaffolding systems in tissue engineering not only aim to serve as a three-dimensional (3-D) substrate but also as growth factor delivery vehicle to promote cellular activity and enhance tissue regeneration. This study aims to supplement existing research on the characterization of porous chitosan scaffolds fabricated using the freeze-gelation method and to optimize the conditions for incorporating poly (lactic-co-glycolic) (PLGA) microspheres into such scaffolds. High porosity and large pore size are essential for tissue engineering scaffolds and could be achieved by higher chitosan concentration and longer duration of gelation time during the synthesis of scaffolds. Two microspheres incorporation strategies investigated were the drop wise method in which the microspheres suspensions were added onto the surface of the scaffold drop by drop and the immersion method whereby the scaffolds were immersed into the microsphere suspension. A comparison of the incorporation efficiency between the two methods was made based on the amount of microspheres incorporated and the cumulative protein release from the scaffolds after incorporation. From the data obtained, microspheres incorporated using immersion method were evenly distributed throughout the scaffold leading to a longer and higher sustained release than those using the drop wise method. The results of this research present the immersion method as a potential energy saving strategy to incorporate microspheres into scaffold other than the drop wise method.